Computed tomography findings of focal lung lesion and their pathological correlations - Sharma, Saroj; Pant, Hom Prasad; Pandit, Swoyam Prakash (Journal of Kathmandu Medical College, 2016)
Background: Focal lung masses are common radiological fi ndings which need to be characterized to plan management. Suspicious lesions require invasive investigations and aggressive treatment. However, likely benign lesions require no invasive investigations. Objectives: We aimed to correlate the computerized tomography fi ndings of focal lung lesions with pathological diagnoses. Methods: A total of 56 patients were enrolled in the study. Plain and contrast enhanced computerized tomography scan of chest was done in spiral computerized tomography. Radiologist’s computerized tomography reports were obtained. Pathological diagnosis were followed in all cases and recorded. Computerized tomography reports were compared with pathological reports and validity of computerized tomography in predicting the nature of lung lesion was assessed. Results: Overall, squalors cell carcinoma was the most common histological cell type (46.34%) followed by adenocarcinoma (41.46%). In 95.12% of total cases, size of the malignant lesion was more than 3cm. Squalors cell Carcinoma was the most common tumor located centrally (71.42%) and adenocarcinoma peripherally (55.55%). Spiculated margin was most commonly associated in malignant lesions. Among morphological characters, chest wall invasion and meditational invasion were statistically significant for malignancy. Contrast enhancement more than 20 hounsfield unit had more than 80% sensitivity and specificity for malignant lesions. Sensitivity of computerized tomography combining all morphological characteristics for depicting malignancy was 97.6% and specificity was 46.7%. Conclusion: The present study showed that contrast enhanced computerized tomography provides more precise tumor localization, characterization and intrathoracic extension to differentiate benign from malignant lung lesion. Enhancement of the lesion is more specific for malignancy than other morphological characteristic. Journal of Kathmandu Medical College, Vol. 4, No. 2, Issue 12, Apr.-Jun., 2015, page: 59-64